PERBEDAAN PENGARUH PENDEKATAN PEMBELAJARAN DAN PERSEPSI KINESTETIK TERHADAP HASIL TEMBAKAN LAY UP BOLABASKET - Herywansyah FKIP (Universitas Tunas Pembangunan, 2011)
The Difference Effect of Learning Approach and Kinestetik Perception Toward Lay Up Shoot Result of Basketball (Experimental Study of Massed Practice and Distributed Practice to Male of Sport and Health Education of Teaching and Learning Faculty of Surakarta Tunas Pembangunan University). Thesis. Surakarta. Postgraduate Program of Surakarta Sebelas Maret University, August 2010. This research aims to find out: (1) the difference between the effect of massed practice and distributed practice to the basketball lay up shoot result, (2) the difference of the basketball lay up shoot result between male students with high and low kinestetik perception, (3) the interaction effect between the learning approaches and kinestetik perception to the basketball lay up shoot result. This research employed an experimental method with 2 x 2 factorial design. The population of the research in the study were the male of Sport and Health Education of Teaching and Learning Faculty of Surakarta Tunas Pembangunan University, as many as 60 students. The sampling technique was purposive random sampling. ANOVA was used to analyzing data, the data analysis prerequisite test was done using the sample normality test (Lilliefors test with Î± = 0.05%) and variance homogeneity test (Bartlett test with Î± = 0.05%). Based on the result of the analysis, conclusions are drawn as follows: (1) There is a difference massed practice and distributed practice to the basketball lay up shoot result. The effect of learning approach distributed practice is better than that learning approach massed practice, (2) there is a difference to the basketball lay up shoot result between the male students with high and low kinestetik perception. The effect to the basketball lay up shoot result between the students with high kinestetik perception is better then the one with low kinestetik perception, (3) there is a effect of interaction between learning approach with kinestetik perception to the basketball lay up shoot result. The students with high kinestetik perception has according if it is learning approach distributed practice. While the students with low kinestetik perception has according if it is learning approach massed practice.